The Struggle for Self-Actualization of Female Characters in The Film Wadjda (2012) a Feminist Review and Abraham Maslow's Hierarchy of Needs - Talia Salma Najihah; Rohanda Rohanda (Gunung Djati Conference Series, 2025)
The film Wadjda (2012), directed by Haifaa al-Mansour, tells the story of a Saudi girl who rebels against gender norms with her ambition to obtain a green bicycle. This study examines Wadjda's psychological journey in fulfilling Abraham Maslow's hierarchy of needs—from basic needs, safety, love and esteem, to self-actualization—within a feminist framework. The method used is a semiotic text analysis of key scenes, combined with a qualitative descriptive approach. The results show that Wadjda's simple act of riding a bicycle becomes a symbol of women's independence and freedom in a patriarchal society, marking the phase of self-actualization. Meanwhile, the roles of the family, school, and patriarchal society reveal the overlapping dynamics of security and self-esteem needs. This study is significant as it enriches feminist scholarship with Abraham Maslow's Hierarchy of Needs Theory in Arab countries from a psychological perspective, and offers a new perspective for analyzing non-Western films within gender and developmental psychology discourse.